EDUKASI MASYARAKAT PENTINGNYA VAKSIN COVID-19 GUNA MENCEGAH PENYEBARAN COVID-19 DI KECAMATAN BIRU-BIRU - Herviani Sari; Firdaus Fahdi (INSTITUT KESEHATAN DELI HUSADA, 2021)
The Covid-19 pandemic has entered a new phase. Efforts to control Covid-19 are carried out by conducting mass vaccinations to all levels of society. Indonesia itself has launched and targeted a vaccination program for all levels of society. This vaccination program aims to achieve herd immunity. Indonesia itself currently uses 6 types of vaccines from several countries, namely vaccines produced by PT Bio Farma (Persero), AstraZeneca, China National Pharmaceutical Group Corporation (Sinopharm), Moderna, Novavax Inc, Pfizer Inc. and BioNTech, Sinovac Life Sciences Co., Ltd. This outreach activity aims to provide understanding and knowledge to the public about the importance of the Covid-19 vaccine. This activity was carried out in Penen village, Biru-Biru District.